2001
DOI: 10.1200/jco.2001.19.22.4238
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Randomized Intergroup Trial of Subtotal Lymphoid Irradiation Versus Doxorubicin, Vinblastine, and Subtotal Lymphoid Irradiation for Stage IA to IIA Hodgkin’s Disease

Abstract: These results demonstrate that it is possible to obtain a high FFS rate in a large group of stage IA to IIA patients without performing staging laparotomy and that three cycles of chemotherapy plus STLI provide a superior FFS compared with STLI alone. Extended follow-up is necessary to assess freedom from second relapse, overall survival, late toxicities, patterns of treatment failure, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 33 publications
4
58
0
3
Order By: Relevance
“…Recently, Ganz et al [2] reported on the results of a prospective study of quality of life and symptoms in patients with early stage HD treated on a clinical trial comparing subtotal nodal irradiation to combined modality therapy [29]. Of note, prior to treatment with any cancer therapy, these patients had scores on the SF-36 Vitality scale that were more than a half standard deviation below the mean of the general population.…”
Section: Prevalence and Correlates Of Fatigue In Hodgkin's Disease Pamentioning
confidence: 99%
“…Recently, Ganz et al [2] reported on the results of a prospective study of quality of life and symptoms in patients with early stage HD treated on a clinical trial comparing subtotal nodal irradiation to combined modality therapy [29]. Of note, prior to treatment with any cancer therapy, these patients had scores on the SF-36 Vitality scale that were more than a half standard deviation below the mean of the general population.…”
Section: Prevalence and Correlates Of Fatigue In Hodgkin's Disease Pamentioning
confidence: 99%
“…Multiple randomized studies revealed that combined modality treatment (RT plus chemotherapy) has superior outcomes and less toxicity to RT alone. Of importance are the two randomized studies by Press et al (Press, LeBlanc, Lichter, et al, 2001) and Engert et al (Engert, Franklin, Eich, et al, 2007) which compared RT alone in early stage favorable HL to combined modality with chemotherapy followed by RT. Press el al compared 3 cycles of chemotherapy (doxorubicin + vinblastine) followed by subtotal lymphoid irradiation (STLI) to STLI alone with freedom from treatment failure (FFTF) of 94% vs. 81% after 3 years of follow up in favor to combined modality arm.…”
Section: Radiotherapy Alonementioning
confidence: 99%
“…The results of large randomized studies comparing RT alone versus combined modality therapy (CMT) have recently been published. [13][14][15][16] These studies include a SWOG trial, 13 the German Hodgkin Study Group (GHSG) HD7 trial, 14 and the EORTC H7 and H8 studies. 15,16 The SWOG study has compared subtotal nodal irradiation (STNI) with a combined modality therapy consisting of chemotherapy (three courses of doxorubicin and vinblastine) followed by STNI.…”
Section: First-line Therapy For Early Stage Diseasementioning
confidence: 99%
“…To reach their conclusions, the experts extensively analyzed large randomized clinical trials conducted in the last 15 years, whose results have been published as full papers [13][14][15][16][17][18][19][20][21] or as abstracts. [22][23][24][25] A number of cohort studies, 3,26,27 and the results of Cochrane analysis on chemotherapy, RT and combined modality for HL 28 have also been considered.…”
Section: First-line Therapy For Early Stage Diseasementioning
confidence: 99%